Refleksi Kritis atas Imajinasi Ekologi Masyarakat Tapanuli Tengah dalam Tradisi "Maragat Tuak Bagot" - Marbun, Martina Rosmaulina; Kaho, Eventus Ombri (Sepakat : Jurnal Pastoral Kateketik, 2025)
This research aims to examine and understand how the tradition of “Maragat Tuak Bagot” (tapping palm sap) in the Batak community in the Central Tapanuli region reflects an ecological imagination that is in line with the principles of Catholic Eco-Theology (Laudato Si). This tradition is a cultural practice that contains ecological and spiritual meaning, in which the Batak people in the Central Tapanuli utilize natural resources in a sustainable manner and with full respect for the environment. Through a Catholic Eco-Theology approach, this research seeks to explore the theological values ​​contained in this tradition and how these values ​​are lived out in society. The research method used is qualitative and literature study. Field data was obtained by conducting in-depth interviews with community leaders and practitioners of the “Maragat Tuak Bagot” tradition. The research results show that the “Maragat Tuak Bagot” tradition not only has a socio-cultural function but also contains deep ecological messages. This practice contains reflections on the importance of maintaining natural balance, respecting creation, and involving the spiritual dimension. Apart from that, the “Maragat Tuak Bagot” tradition also represents the relationship between humans and nature which is in line with Catholic Eco-Theological teachings about human’s moral responsibility to care for the earth as a shared home. The results of this research provide an important contribution in enriching the discourse on ecology and theology in Indonesia, as well as offering a new perspective in environmental conservation efforts based on local wisdom and religious values.